Oscillations of the electrical resistance induced by shear deformation in molten carbon black composites - Krückel, Johannes; Stary, Zdenek; Schubert, Dirk W. (Polymer, 2013)
The time-dependent electrical resistance of polymethylmethacrylate containing carbon black was monitored under oscillatory shear in the molten state. The electrical signal measured was oscillating exactly at the doubled frequency of the oscillatory shear deformation. Moreover, the experimental results gave a hint to the development of conductive structures in polymer melts under shear deformation. It was shown that the flow induced destruction of conductive paths dominates over the flow induced build-up in the beginning of the shear deformations. However, for longer times both competitive effects reach a dynamic equilibrium and only the thermally induced build-up of pathways influences the changes in the composite resistance during the shear. Moreover, the oscillating electrical response depends clearly on the deformation amplitude applied. Furthermore, a simple physical model describing the behaviour of conductive pathways under shear deformation was derived and utilized for the description of the experimental data.
Keywords: Polymer composites; Electrical resistance; Rheology